Ordini marcati delle parole nell'italiano scritto: apprendenti germanofoni, apprendenti anglofoni e parlanti nativi a confronto - Valentini, Ada (Incontri. Rivista europea di studi italiani, 2018)
Marked word orders in written Italian A comparison between native speakers, L1-German learners, and L1-English learnersThis paper focuses on cross-linguistic influence in the acquisition of Italian as an L2 by learners with Germanic L1s (English and German). The general domain under investigation is information structure, notably marked word orders. The English and German languages differ from each other in this domain, since English has a rigid word order (SVO), while German is a Verb-second language, with a relatively flexible word order. The hypothesis tested in this study is that English learners are more reluctant to deviate from a basic word order SVO in response to information structure than their Germans pairs. Approximately 300 written texts were selected from two comparable corpora freely available online, VALICO and VINCA. VALICO is an Italian corpus which includes narratives produced by Italian L2 learners and VINCA is the corresponding control corpus produced by native Italian speakers. Data analysed in this paper lend support to the hypothesis that English learners are more prone to conform to the basic SVO word order pattern than German speakers: They apparently avoid VS orders with inaccusative verbs and overuse presentational sentences with esserci, which are largely employed in their L1. In the last section of the paper some instructional interventions to foster the noticing of marked word orders and their relative functions will be suggested.